Pernikahan Dini Pada Remaja Putri: Evaluasi Kualitas Asuhan Kebidanan di Layanan Antenatal Care dan Rekomendasi Kebijakan Pencegahan di Kabupaten Sambas – A Systematic Literature Review - Megawati; Nabila Husna; Dufi Roma Dini; Neneng Santi Purnawati; Lisa Trina Arlym (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Early marriage remains a public health problem in developing countries, including Indonesia. Adolescents who marry before the age of 18 are at higher risk of pregnancy complications and low utilization of quality antenatal care (ANC) services. This study aims to evaluate the impact of early marriage on the quality of midwifery care in antenatal care (ANC) services, and to provide evidence-based prevention policy recommendations. This study is a systematic literature review (SLR) of articles published in the last five years (2019–2024) and retrieved from five electronic PubMed, ScienceDirect, SpringerLink, EBSCOhost, and ProQuest. The selection process followed the PRISMA 2009 process. Inclusion criteria were determined based on the PICOS approach, and article quality was assessed using the Center for Evidence-Based Medicine (CEBM) critical appraisal tool. Results: A total of three articles met the inclusion criteria. The study was conducted in Nigeria, Pakistan, and Sub-Saharan Africa, using a cross-sectional and retrospective design based on secondary data (DHS and MICS). The results show that early marriage is negatively correlated with the frequency and quality of ANC visits, including delays in the first visit and poor access to skilled health workers. Sociodemographic factors, education, residence, and social security are the main determinants. Early marriage negatively impacts the quality of midwifery care in ANC services. Cross-sectoral policies are needed to prevent early marriage and strengthen youth-friendly midwifery services, particularly in rural areas.